Design and implementation of a centralised database system for doctor profiles with digital signage integration at UTAR Hospital - Tew, Chia Li (2025)
This project focuses on the area of Health Informatics, specifically addressing the inefficiencies in managing and presenting doctor profiles within UTAR Hospital. The traditional method of maintaining doctor information across multiple platforms often leads to data duplication, inconsistency, and inefficient dissemination to the public. To resolve this, the project proposes the design and implementation of a centralized database system integrated with a digital signage interface. The system was developed using the Frappe Framework, which provides a robust backend for database management via user-friendly forms called Doctypes. This enabled hospital administrative staff to insert, update, or delete doctor profiles without needing technical knowledge. Each profile contains multilingual details including name, qualifications, specialization, and contact information. The methodology involved three major stages: (1) designing the database and Doctype structures, (2) developing a responsive doctor profile web page for digital signage using HTML, CSS, and JavaScript, and (3) hosting the display system on a local network accessible via IP address. System testing confirmed that the solution met all requirements, including real-time profile updates, slideshow presentation, and secure local access. The novelty of this project lies in its integration of a database-driven web interface directly into the hospital’s digital signage system, without third-party tools or APIs. This approach ensures data consistency, low maintenance, and real-time updates across all displays. This project concludes with a fully functional and scalable system, improving both internal data management and external communication with patients and visitors.